Background Music Dependent Reduction of Aversive Perception and Its Relation to P3 Amplitude Reduction and Increased Heart Rate - Matsuo, Masahiro; Masuda, Fumi; Sumi, Yukiyoshi; Takahashi, Masahiro; Yoshimura, Atsushi; Yamada, Naoto; Kadotani, Hiroshi (Frontiers in Human Neuroscience, 2019)
Music is commonly used to modify mood and has attracted attention as a potential therapeutic intervention. Despite the well-recognized effects of music on mood, changes in affective perception due to music remain majorly unknown. Here, we examined if the perception of aversive stimuli could be altered by mood-changing background music. Using subjective scoring data from 17 healthy volunteers, we assessed the effect of relaxing background music, busy background music, or no background music conditions on response to aversive white noise stimulation. Interestingly, affective response to the white noise was selectively alleviated, and white noise-related P3 component amplitude was reduced in busy background music. However, affective responses as well as P3 amplitude to reference pure tone stimuli were similar regardless of background music conditions. Interestingly, heart rate increased in busy background music, whereas no increase in heart rate was found in similar distress, no background music condition. These findings suggest that increase in heart rate, which happens during busy background music exposure, can be a reflecting feature of music that ameliorate the affective response to aversive stimuli, possibly through selective reduction in neurophysiological responses.